'It's the soft stuff that's hard': Investigating the role played by low carbon small- and medium-sized enterprise advisors in sustainability transitions. (June 2018) - Hampton, Sam
Significant public funds are invested in low carbon advisors to support small- and medium-sized enterprises to reduce carbon emissions on a regional basis. Little research has been conducted on their experiences and practices, nor their place within the context of local business support policy. Findings draw on interviews with 19 advisors in the UK as well as the author's four years' experience as an environmentally focused business support practitioner. Establishing and sustaining engagements with small- and medium-sized enterprises on the topic of pro-environmental behaviours is a multifaceted problem. Advisors typically approach businesses with promises of cost savings rather than using environmental messaging and focus their resources on the provision of building energy audits and technical advice. Advisors rarely engage small- and medium-sized enterprises in values-based discussions or by seeking to understand how and why energy is used in the course of everyday business practices. The paper argues that face-to-face meetings could be better utilised if 'softer' skills were deployed alongside technical expertise. It discusses the limitations of growth-focused support in the context of environmental objectives and calls for a shift in the culture of advice-giving, supported by social scientifically informed policy.